Duckling body mass increases with abundant aquatic invertebrates: Experimental approach - Basile Marteau; Janne Sundell; Roosa Pesonen; Petri Nummi (Global Ecology and Conservation, 2025)
In Fennoscandia, waterbirds have declined over several decade, and this decline could be linked to problems in the breeding success and loss of foraging habitat provided by wetlands. Availability of aquatic invertebrates is crucially important for ducks during the breeding season, and especially for young ducklings. However, the relationship of invertebrate food resources on duckling growth and survival is not very well understood. In this research, we used imprinted mallard ducklings (Anas platyrhynchos, 1758) to study the effect of the availability of aquatic invertebrates on duckling growth. At hatch, ducklings were divided into two different groups and assigned to forage either on permanent (lakes) or temporary (ponds) wetlands. Each day, ducklings were brought to the study sites for four hours to forage. Ducklings were weighed before and after the foraging period. Aquatic invertebrates were sampled with activity (macroinvertebrates and zooplankton) and emergence traps (aquatic emerging insects). The ducklings gain more weight in temporary ponds, and this was associated with the availability of macroinvertebrates. Temporary ponds had higher aquatic macroinvertebrate abundance than the permanent lakes. However, no significant relationship was found between duckling weight and abundance of emerging insects or zooplankton. We highlight the crucial role of aquatic invertebrates in ducklings’ mass gain and emphasize the importance of temporary wetlands during the brood rearing period for the breeding success of ducks.